(3EfSGf GdYjhf aj SjQI GdCejf GdeCehf Udi Gddg Ydjg hSdes - (3GdMdHj, CHh GdaQL, GHf HQgGf GdOjf, fhQ GdOjf, Ydj Hf EHQGgje Hf CMeO, J (B1044 (3g`s ((3YHO Gddg eMjj GdOjf Hf Jbj GdOjf GdOeTbj GdSdWjs)
(3ChdgG (B:s
(3HGH HOA GdBPGf heTQhYjJg Cj hGdEbGeI heTQhYjJgG cd efgeG ef NUGFU gPg GdCeI ceG Cf ef NUGFUgG GdQchY hGdLeGYI hGaJJGM GdUdGI HGdJcHjQs
(3BNQgG (B:s
(3ceG HGQcJ Ydi EHQGgje hYdi EHQGgje hYdi Bd EHQGgje aj GdYGdejf Efc MejO eLjO hGNJe dfG HNjQ hGUdM dfG TCffG cdg hGaYd Pdc HENhGffG hCMHGHfG hSGFQ GdeSdejf hGSJZaQ Gddg ef bhd HdG Yeds
(3GdeJf GdCUdj eMGW HEWGQ HGddhf GdCMeQ eY HYV GdLOGhd GdUZjQI ddCHjGJ GdTQYjI OGNd UdH GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 251s
(3eYLe GdeDdajf(B: 2 / 386s
(3cTa GdXfhf(B: 1 / 180s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs